2022
DOI: 10.3390/healthcare10071226
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the Work Engagement of UK Active Employees

Abstract: The objective of this investigation was to describe the work engagement perceived by UK workers during the COVID-19 pandemic. A descriptive cross-sectional study was conducted. The sample included 1085 participants, aged 18 years and older, living in the UK during the COVID-19 pandemic, who were active workers. Data were collected using an online questionnaire and the UWES-9. They were analysed using descriptive statistics, a t-test for equality of means or ANOVA, and the Chi-squared Automatic Interaction Dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…In another study conducted in Spain on nonhealthcare workers, it was found that at low levels of engagement there were higher percentages of psychological distress (77.9%), and this same trend was observed both in the group of workers who worked away from home and among those who worked from home (11). Following this, a study conducted in the UK on 1,038 general workers (44), in line with a study conducted in New Zealand on 530 social workers (10), found that work engagement was an effective predictor of reduced burnout, cynicism, and feelings of reduced professional competence.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In another study conducted in Spain on nonhealthcare workers, it was found that at low levels of engagement there were higher percentages of psychological distress (77.9%), and this same trend was observed both in the group of workers who worked away from home and among those who worked from home (11). Following this, a study conducted in the UK on 1,038 general workers (44), in line with a study conducted in New Zealand on 530 social workers (10), found that work engagement was an effective predictor of reduced burnout, cynicism, and feelings of reduced professional competence.…”
Section: Discussionmentioning
confidence: 71%
“…The initial search strategies identified a total of 704 references, which were screened according to the topic of this review. A total of 24 studies (5,10,11,15,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) were finally selected (Figure 1). All the analysed studies were quantitative.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the reason for the high work engagement among married people is deemed to be originated by accountability, high involvement in work and emotional stability of married people and the extra support that they get from their families [ 106 ]. In a similar study conducted after the onset of the Covid-19 pandemic, considerably higher work engagement was noticed in people who were married or living with a partner, with children under 16 years of age, and with a very good perception of health in the last 14 days [ 32 ]. As a result, marital status and having children were found to be important factors in flexible workers after Covid-19.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it has been observed that the attitude towards flexible working options varies depending on gender, sector and previous participation in flexible working [ 48 ]. After the Covid-19 pandemic, research related to flexible working has increased and gained importance [ 32 , 65 ]. Especially, studies concerning the additional burden of women in housework and childcare is frequently discussed [ 66 ].…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation